Efficacy of Heat Patch Applied on Lower Back for Reducing Postoperative Pain after Cesarean Delivery: A randomized controlled trial - Sitthisaknawakul, Wilanee; Chantanavilai, Sathida (Thai Journal of Obstetrics and Gynaecology, 2025)
Objectives: To study the efficacy of using a heat patch to reduce postoperative pain after cesarean delivery. Materials and Methods: Women who underwent cesarean delivery under a spinal block were randomly allocated into two groups, comprising one group who received a heat patch and one who received standard postoperative care. The heat patch group received a 40-degree Celsius heat patch applied to the lower back (dermatome T10 to L1) 6 hours postoperatively, while the control group received standard postoperative pain control. The primary outcome was assessed based on postoperative pain scores at 8 hours using a 10-cm visual analogue scale (VAS). Results: Seventy-eight postoperative women, 39 in each group, were recruited between September 2023 and March 2024. The heat patch group expressed significantly less postoperative pain than the control group 8 hours after cesarean delivery (3.5 ± 0.3 vs 4.7 ± 0.4; mean difference 1.2; 95%CI: 0.4-2.1; p = 0.006). The time to first ambulation in the heat patch group was significantly shorter than the control group (1,073 ± 267.7 min vs 1,261.9 ± 205.3 min; mean difference 189 min; 95%CI: 81.4-296.6; p < 0.001). The heat patch group required fewer additional analgesic drugs compared to the control group (56.4% vs 82.1%; p = 0.014). No adverse events were reported. Conclusion: A heat patch applied on the lower back resulted in significantly reduced pain 8 hours after cesarean delivery.